2014
DOI: 10.1186/1556-276x-9-288
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of HDPE/N-MWNT nanocomposite films

Abstract: In this work, a series of nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) with several weight percentages (0.1, 0.4, 0.8, and 1.0 wt.%) were synthesized by catalytic chemical vapor deposition (CCVD) technique. The N-MWCNTs were first characterized and then dispersed in high-density polyethylene (HDPE) polymer matrix to form a nanocomposite. The HDPE/N-MWCNT nanocomposite films were prepared by melt mixing and hot pressing; a good dispersion in the matrix and a good N-MWCNT-polymer interfacial adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The different types of nanofillers have been used to strengthen and toughen the polymers. The most interesting aspect related to nanofiller is that they can improve the properties of polymers at very low filler concentrations compared to micro-particles and fibers [79]. This phenomenon can be described as nanoeffect which is the interactions at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…The different types of nanofillers have been used to strengthen and toughen the polymers. The most interesting aspect related to nanofiller is that they can improve the properties of polymers at very low filler concentrations compared to micro-particles and fibers [79]. This phenomenon can be described as nanoeffect which is the interactions at the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…The proton resonances of anchored APND in MWCNTs-APND were broader and weaker than those of the APND. The signal from protons of MWCNTs-APND is not split and shifted up-field, which is likely attributed to the interaction between MWCNTs and APND, as well as magnetic-field induced partial orientation of MWCNTs [20,21], indicating that APND is attached on the surfaces of MWCNTs via amide linkages.…”
Section: Scheme 1 Schematic Image Of Mwcnts Modified With 2-(4-aminopmentioning
confidence: 82%
“…Chrissafis et al [4] have observed that addition of SiO 2 nanoparticles enhances the mechanical and thermal properties. It is also reported that the addition of modified MWCNT to HDPE results in the formation of nanocomposite films without loss of crystallinity [5]. Jiang et al [6] have studied the electrical conductivity and mechanical properties of HDPE reinforced with coated graphene platelets and MWCNT.…”
Section: Introductionmentioning
confidence: 97%